2011
DOI: 10.1111/j.1747-0803.2010.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Berry Syndrome Type 2B

Abstract: We present a case of a 34-day-old baby boy with congestive heart failure and differential cyanosis. Based on echocardiography and confirmed with computed tomography angiography, the following abnormalities were detected: aortopulmonary window, aortic origin of the right pulmonary artery, patent ductus arteriosus, and hypoplasia/coarctation of the aorta. No other congenital abnormalities were detected, and a diagnosis of Berry Syndrome type 2B was made. No preoperative cardiac catheterization or angiocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…The literature consists of anecdotal case studies performed by different surgeons throughout the world (Table 2). [2][3][4][5][8][9][10][11][12][13][14][15][16][17] Most centers advocate one-stage surgery in the neonatal period, although Ghelani and colleagues 5 suggested that a staged repair should be considered in premature infants or small-forgestational-age infants. We also recommend surgical correction should be performed as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The literature consists of anecdotal case studies performed by different surgeons throughout the world (Table 2). [2][3][4][5][8][9][10][11][12][13][14][15][16][17] Most centers advocate one-stage surgery in the neonatal period, although Ghelani and colleagues 5 suggested that a staged repair should be considered in premature infants or small-forgestational-age infants. We also recommend surgical correction should be performed as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging confirmation of brain death is usually sought to accelerate this process. A scintigraphic brain death study is noninvasive, simple to perform even in the intensive care unit (ICU) setting (portable) and reliable, making it the modality of choice to establish imaging evidence supporting the clinical diagnosis of brain death [14][15][16][17]. From a clinical standpoint, this diagnosis requires the patient to be in a deep coma, with total absence of brainstem reflexes or spontaneous respiration.…”
Section: Brain Perfusion Study For Brain Death Diagnosismentioning
confidence: 99%
“…Patients with Berry syndrome present with respiratory distress, metabolic acidosis, anuria, severe congestive heart failure or acute cardiovascular collapse with spontaneous closure of ductus arteriosus in the first few days of life. Early clinical diagnosis with detailed preoperative recognition of these unique anatomic features is therefore essential for good surgical outcomes [2,3,[5][6][7]. Long-term follow-up is required after surgical correction as stenosis at the site of anastomosis is a potential complication.…”
Section: Discussionmentioning
confidence: 99%
“…Aortopulmonary window has been classified based on the location of the septal defect [1,2]. Type I comprises proximal communication with normal origin of pulmonary arteries.…”
Section: Introductionmentioning
confidence: 99%